Combustion Conduct Of A Single-Cylinder Spark-Ignition Affected By Ethanol Fuel Mixtures of Supplement Hydroxy Gas (HHO) - Kholili, Navik; Setyono, Gatot (Jurnal Teknik Mesin, 2021)
Ethanol is an alternative fuel to replace fossil fuels. Ethanol's high octane value can substitute for power in spark-ignition engines (SI). Gasoline mixed with ethanol will reduce the calorific value generated and intensify the combustion process in the combustion chamber. Through the engine performance test, we can find out the increase in the performance of the SI engine. Several essential variables can improve engine performance, such as gasoline-ethanol variations, iridium spark plugs, and hydroxy gas generators (HHO). This research uses an experimental method by utilizing gasoline (octane-92)-ethanol variations (35%, 45%, and 55% v/v) with the intake of hydroxy gas during the combustion process. The SI automatic transmission engine has a capacity of 124.8 cubic centimeters (one cylinder-four stroke), a compression ratio of 11/1, fuel injection, and iridium spark plugs. Engine performance test using chassis dyno test with engine speed variations of 4000-9000 rpm. This study resulted in optimal performance on a 55% increase in gasoline-ethanol mixture with an intensify in output-power, pressure, and thermal efficiency at an engine-speed of 8000 rpm. It is contrary to the specific fuel consumption has decreased.